Acid-happy: Survival and recovery of enteropathogenic Escherichia coli (EPEC) in simulated gastric fluid. (March 2019) - Pienaar, Jennifer Anne; Singh, Atheesha; Barnard, Tobias George
Abstract: Background: Gastric fluid pH serves an important function as an ecological filter to kill unwanted microbial taxa that would otherwise colonise the intestines, thereby shaping the diversity and composition of microbial communities found in the gut. The typical American-based diet causes the gastric pH to increase to pH 4 to 5, and it takes ∼2 h to return to pH 1.5 (normal). This window of increased gastric pH may allow potential pathogens to negotiate the hostile environment of the stomach. Another factor to consider is that in developing countries many people experience hypochlorhydria related to malnutrition and various gastric diseases. Enteropathogenic E. coli (EPEC) is a leading cause of infantile diarrhoea and has a high incidence in the developing world. The aim of this study was to assess the survival and recovery of non-acid adapted EPEC exposed to simulated gastric fluid (SGF) over a period of 180 min. Results: EPEC were grown in nutrient-rich medium and acid challenged in SGF at pH 1.5, 2.5, 3.5 and 4.5. Culturability was evaluated using a standard plate count method, and metabolic viability was assessed via cellular energy (adenosine triphosphate [ATP] assay) and respiratory activity (3-bis(2-methyloxy-4-nitro-5-sulfophenyl)-5-[(phenylamino)carbonyl]-2H-tetrazolium hydroxide [XTT] assay), and recovery and proliferation by means of optical density in liquid cultures. Sampling was performed at 0, 30, 60, 120, and 180 min post-SGF exposure. The results of this study showed that EPEC is remarkably acid resistant and was able to survive a simulated gastric environment for up to 3 h (180 min) at various pH (1.5, 2.5, 3.5, and 4.5). EPEC was culturable at all pH (1.5, 2.5, 3.5 and 4.5) at the higher inoculum size of 5.4–7.1 × 10 6 CFU/ml, and at all pH except pH 1.5 at the lower inoculums of 5.4–7.1 × 10 3 CFU/ml or 5.4–7.1 × 10 1 CFU/ml. The organism remained metabolically viable at pH 1.5, 2.5, 3.5, and 4.5 and was able to recover and proliferate once placed in a neutral, nutrient-rich environment. Conclusion: In this study, EPEC demonstrated remarkable acid resistance and recovery at low pH without prior acid adaptation, which could prove to be problematic even in healthy people. In individuals with decreased gastric acidity, there is a higher probability of pathogen colonization and a resulting change in the gut microbiome. The results highlight the potential increase of food- and waterborne diseases in persons with compromised gastric function, or who are malnourished or immunocompromised. The data herein may possibly help in calculating more precisely the risk associated with consuming bacterial contaminated food and water in these individuals. Highlights: EPEC are able to survive exposure to simulated gastric fluid (SGF) for up to 3 h. EPEC showed continued cellular energy and respiration for up to 3 h SGF exposure. EPEC were able to form colonies after exposure to SGF for up to 3 h. EPEC showed recovery after up to 3 h SGF exposure once placed in neutral media.